128Non-invasive 3D mapping of earliest activation of premature ventricular complexes originating from intracardiac structures to guide catheter ablation. (18th June 2020) - Vali, Z; Mistry, A; Velu, S; Sidhu, B; Li, X; Pooranachandran, V; Lazdam, M; Ibrahim, M; Sandilands, A; Somani, R; Stafford, P; Ng, G A
Abstract: Funding Acknowledgements: Research funding from Catheter Precision, Inc. Introduction: Catheter ablation for ventricular arrhythmias such as premature ventricular complexes and ventricular tachycardia is an established management approach.  Non-invasive mapping to localise the earliest activation (site of origin) on the myocardium may help guide ablation.  Established ECGi methods using the inverse solution to reconstruct epicardial electrograms are unable to accurately locate arrhythmias from the endocardium or from intracardiac structures.  VIVO™ (Catheter Precision) is a novel vectorcardiography based 3D mapping system that may be able to localise arrhythmias from any part of the ventricle. Methods: We reviewed our initial experience utilising this mapping system to guide catheter ablation of ventricular ectopics from the inter-ventricular septum, coronary cusp or papillary muscle.  A patient-specific 3D heart and torso model was created using semi-automated segmentation of MRI or CT scan images.  A 3D topographic image of the patient's torso was taken to accurately position surface ECG electrode locations onto the 3D heart-torso model.  An ECG of the PVC was imported from LabSystemPro (Bard) into VIVO™ for analysis prior to ablation.  The result was then compared with the site of earliest activation identified using invasive electro-anatomical (EA) mapping. Results: VIVO™ was used in 12 cases where the PVC was localised to an intracardiac structure – six papillary muscle, four to the septum and two from the coronary cusp.  VIVO™ was able to accurately localise the earliest activation site when compared to the invasive map in 5/6 papillary muscle cases, 3/4 septal cases and 2/2 coronary cusp cases.  Ablation was acutely successful in all cases.  One additional patient had a PVC localised non-invasively to the postero-medial papillary muscle, however an invasive 3D electro-anatomical map or ablation was not performed. In three cases we were able to merge the 3D geometry of the non-invasive map from VIVO™ into the Carto™ system to guide mapping and ablation in real time (see figure). Conclusion: Our experience shows promising results for accurate non-invasive localisation of ventricular arrhythmias originating from intracardiac structures.  Non-invasive localisation is of particular value in cases where the arrhythmia is infrequent, difficult to induce or poorly tolerated haemodynamically.  The two cases where PVC localisation was inaccurate were performed using an older version of the software. With recent refinements, localisation is anticipated to be improved further. We also present the first experience of combining the VIVO™ geometry with the real-time invasive EA map.  This has potential to significantly speed up mapping time and reduce the need for expensive multi-polar catheters by allowing the operator to see their target in real time 3D.  Further work is ongoing to validate the accuracy of VIVO™ prospectively and quantitatively.